The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00027-010-0165-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food web structure on the biochemical composition of seston, zooplankton and recently deposited sediment in experimental freshwater mesocosms

Abstract: The effects of food web structure on the quantity and biochemical composition of seston, zooplankton and recently deposited sediment in experimental freshwater mesocosms were examined. Food web structure was manipulated by addition of zooplanktivorous fish. Biochemical characterisations were carried out using lipid biomarkers (sterols, fatty acids, chlorophyll-derived compounds and long-chain alkanediols). Fish addition decreased zooplankton biomass and increased seston biomass and deposited sediment through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 66 publications
2
26
1
1
Order By: Relevance
“…As such, the data should be considered to be qualitative. The chemical analysis of the free lipids extracted from seston (0.7-50 lm fraction) and zooplankton fractions (Allard et al, 2011) indicated that seston and zooplankton compartments were adequately separated by our screening size.…”
Section: Free Lipid Analysismentioning
confidence: 99%
“…As such, the data should be considered to be qualitative. The chemical analysis of the free lipids extracted from seston (0.7-50 lm fraction) and zooplankton fractions (Allard et al, 2011) indicated that seston and zooplankton compartments were adequately separated by our screening size.…”
Section: Free Lipid Analysismentioning
confidence: 99%
“…Lipids containing sterols were isolated and analysed as previously described (Allard et al, 2011). Lipids containing sterols were isolated and analysed as previously described (Allard et al, 2011).…”
Section: Lipid Analysismentioning
confidence: 99%
“…These authors first confirmed that sedimentation rates were higher in fish enclosures than in fishless ones. Moreover, Allard et al (2011) showed that the relative abundance of polyunsaturated fatty acids was higher in RDS from fish enclosures than in RDS from fishless ones. In fish-dominated mesocosms, where zooplankton grazing on phytoplankton was low, sediment N ⁄ P ratio was positively correlated to seston N ⁄ P ratio, suggesting a major contribution of seston to sedimentation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations